Biophysical Properties of Optogenetic Tools and Their Application for Vision Restoration Approaches - Klapper, Simon D.; Swiersy, Anka; Bamberg, Ernst; Busskamp, Volker (Frontiers in Systems Neuroscience, 2016)
Optogenetics is the use of genetically encoded light-activated proteins to manipulate cells in a minimally invasive way using light. The most prominent example is channelrhodopsin2 (ChR2), which allows the activation of electrically excitable cells via light-dependent depolarization. The combination of ChR2 with hyperpolarizing-light-driven ion pumps such as the Cl- pump halorhodopsin (NpHR) enables multimodal remote control of neuronal cells in culture, tissue, and living animals. Very soon, it became obvious that this method offers a chance of gene therapy for many diseases affecting vision. Here, we will give a brief introduction to retinal function and retinal diseases. Optogenetic vision restoration strategies will be highlighted. We will discuss the functional and structural properties of rhodopsin-based optogenetic tools and analyze the potential for the application of vision restoration.